Decision to quit work in bank employees: A phenomenological study - Indah Fatmawati; Marina Sulastiana; Anissa Lestari Kadiyono; Zainal Abidin (Institut Agama Islam Negeri Langsa, 2025)
This study examines the impact of job satisfaction on bank employees' decisions to resign following a corporate merger. Using a qualitative phenomenological approach, the research involved in-depth interviews with three former employees of a merged banking institution in Indonesia, aged between 25 and 35 years, each with over three years of service at the institution. Participants were selected purposively based on their direct experience of working within the post-merger environment and subsequently choosing to resign. Thematic analysis was used to interpret the data, guided by Spector's (1997) dimensions of job satisfaction. The findings revealed a significant decline in employee satisfaction across several key domains, including compensation, leadership, promotion opportunities, workload, and workplace communication. The merger led to increased job demands, reduced perceived fairness, and deteriorating interpersonal dynamics, which collectively contributed to employees' decisions to quit. These results underscore the importance of managing human resource transitions during organizational change. The study emphasizes the importance of transparent communication, equitable workload distribution, and fair compensation systems in post-merger integration strategies to mitigate turnover intentions and promote sustainable organizational growth.